Genetic and Phenotypic Characterization of Indole-Producing Isolates of Pseudomonas syringae pv. actinidiae Obtained From Chilean Kiwifruit Orchards - Flores, Oriana; Prince, Camila; Nuñez, Mauricio; Vallejos, Alejandro; Mardones, Claudia; Yañez, Carolina; Besoain, Ximena; Bastías, Roberto (Frontiers in Microbiology, 2018)
In recent years, Chilean kiwifruit production has been affected by the phytopathogen Pseudonomas syringae pv. actinidiae (Psa), which has caused losses to the industry. In this study, we report the genotypic and phenotypic characterization of 18 Psa isolates obtained from Chilean kiwifruits orchards between 2012 and 2016 from different geographic origins. Genetic analysis by MLSA using four housekeeping genes (gyrB, rpoD, gltA and gapA) and the identification of type III effector genes suggest that the Chilean Psa isolates belong to the Psa Biovar 3 cluster. All of the isolates were highly homogenous in regard to their phenotypic characteristics. None of the isolates were able to form biofilms over solid plastic surfaces. However, all of the isolates formed cellular aggregates in the air-liquid interface. All of the isolates, except for Psa 889, demonstrated swimming motility, while only isolate Psa 510 demonstrated swarming motility. The biochemical profiles of the isolates revealed differences in 22% of the tests in at least one Psa isolate when analysed with the BIOLOG system. Interestingly, all of the isolates were able to produce indole using a tryptophan-dependent pathway. PCR analysis revealed the presence of the genes aldA/aldB and iaaL/matE, which are associated with the production of indole-3 acetic acid (IAA) and indole-3 acetyl-3-L-lysine (IAA-Lys), respectively, in Pseudomonas syringae. In addition, IAA was detected in the cell free supernatant of a representative Chilean Psa strain. This work represents the most extensive analysis in terms of the time and geographic origin of Chilean Psa isolates. To our knowledge, this is the first report of Psa being able to produce IAA. Further studies are needed to determine the potential role of IAA in the virulence of Psa during kiwifruit infections and whether this feature is observed in other Psa biovars.